Evaluation the outcomes of using iliac bone graft for reconstruction of traumatic orbital floor fractures - Mukhalled Salim Alasady; Amer Kanj; Abd El Hadi Kanj (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Orbital floor fracture is common in facial trauma patients. Although surgical repair, the orbital floor fractures are associated with risk of persisting sensibility disorders, enophthalmos and permanent diplopia due to complex antatomy of the orbit,time of surgery & the reconstructive material used for such repairing. Failure of early recognition and treatment of these traumatic injuries may result in  functional and cosmetic problems. Autogenous bone grafts are the gold standard for reconstruction of maxillofacial defects. The iliac crest is also considered the most ideal donor site for bone grafting when a large amounts of bone is needed.Objective : To assess the outcome of early repair of orbital floor fractures in regard to enophthalmos, double vision ,extrusion and gait disturbance.Patients and methods: A total of 15 patients, all with orbital floor fracture, were enrolled 12 of them were having pure blow-out fractures and 3 patients had impure blow-out fractures, all were underwent primary surgical reconstruction of the orbital floor by autogenous anterior iliac crest within 5 – 14 days after injury.Results: The results were well represented as the following: Post-operative complications at recipient site included diplopia (13.3%) Enophthalmos (6.7%) and extrosion (6.7%). At the donor site one patient had pain and another one had gait disturbances, both relieved within one month after treatment.Conclusions: Less complications had been reported post operatively with the use of  non vascularized autogenous iliac bone graft .